Implikasi Undang-Undang Pengadaan Tanah bagi Pembangunan untuk Kepentingan Umum terhadap Penyelesaian Konflik Pengadaan Tanah - Larasati, Meka Azzahra; Sujadi, Suparjo (Fakultas Hukum, Universitas Muslim Indonesia, 2021)
This study aims to evaluate and analyze legal certainty in resolving conflicts over land acquisition for development in the public interest in the context before and after the enactment of Law No. 2 of 2012. The research uses a normative legal research method with a statute approach. The method of analysis in this study is to use qualitative analysis. The study results indicate that legal certainty in resolving conflicts over land acquisition for development in the public interest in the context before and after the enactment of Law No. 2 of 2012, obviously very different. However, from the two cases, land acquisition and compensation for land rights for development in the public interest have not been processed and run effectively. Based on this conclusion, it is recommended that laws and regulations on land acquisition for development in the public interest be more clarified, particularly regarding deliberation activities and the form/amount of compensation value. In addition, all stakeholders involved in negotiating the agreement must attach importance to the principle of deliberation and consensus regarding land acquisition for development in the public interest.